2017
DOI: 10.1039/c7ra05579j
|View full text |Cite
|
Sign up to set email alerts
|

New cyclometalated Ir(iii) complexes with NCN pincer and meso-phenylcyanamide BODIPY ligands as efficient photodynamic therapy agents

Abstract: A new class of cyclometalated iridium(iii) with NCN pincer and meso-phenylcyanamide BODIPY ligands has been synthesized and studied for photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 67 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…Compared to the large number of Ru­(II) systems that have been explored, investigations on Ir­(III) complexes for in vitro PDT have emerged in recent years. Although Ir­(III) complexes derived from diimine ligands (N^N) may fall short of the optimal absorption window for PDT, we have demonstrated that incorporation of two cyclometalating ligands (C^N) to form biscyclometalated Ir­(III) complexes extends the ground-state absorption spectrum significantly and that installation of a π-extended N^N ligand alongside the two C^N ligands extends the lifetime through population of 3 IL states. The result is nanomolar PDT potency with phototherapeutic indices (PIs) greater than 400 .…”
Section: Introductionmentioning
confidence: 98%
“…Compared to the large number of Ru­(II) systems that have been explored, investigations on Ir­(III) complexes for in vitro PDT have emerged in recent years. Although Ir­(III) complexes derived from diimine ligands (N^N) may fall short of the optimal absorption window for PDT, we have demonstrated that incorporation of two cyclometalating ligands (C^N) to form biscyclometalated Ir­(III) complexes extends the ground-state absorption spectrum significantly and that installation of a π-extended N^N ligand alongside the two C^N ligands extends the lifetime through population of 3 IL states. The result is nanomolar PDT potency with phototherapeutic indices (PIs) greater than 400 .…”
Section: Introductionmentioning
confidence: 98%
“…Although this construct was ultimately effective as a ratiometric oxygen probe, synthesis of this sensor required at least 10 steps to prepare the uorophore/ linker construct, which was then coupled to the cyclometalated iridium fragment in 19% yield. There are some known constructs which combine bis-cyclometalated iridium complexes with BODIPY uorophores, [53][54][55][56][57][58] offering the advantages of BODIPY's high uorescence quantum yields and biological compatibility, 59-62 but these have not been developed as ratiometric oxygen sensors. Inspired by this previous work, here we introduce a class of ratiometric sensors prepared by a simple, modular approach, offering rapid access to several sensors with a range of emission proles and ratiometric responses.…”
Section: Introductionmentioning
confidence: 99%
“…Both molecules exhibited low luminescence quantum yields but high  ∆ when irradiated at 500 nm in MeCN (Table 2). As a result, these complexes were able to induce sc-DNA photocleavage and displayed high photocytotoxicity on HeLa cells (IC 50 < 1 µM, PI = 113) while they were poorly active on the non tumorigenic cell line MRC-5 [88]. In a piece of work by Zhao and coworkers, the Ir(ppy) 2 (bpy) entity was attached via πconjugation with an alkynyl linker to the 6-position of the BODIPY core to maximize the heavy atom effect.…”
Section: Metal-bodipy Bioconjugates For Photodynamic Therapymentioning
confidence: 99%